2018
DOI: 10.1016/j.jsps.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the systemic lipopolysaccharide mediated neuroinflammation: Appraising the effect of l -cysteine mediated hydrogen sulphide on it

Abstract: The present research was ventured to examine the effect of l-cysteine on neuro-inflammation persuaded by peripheral lipopolysaccharides (LPS, 125 μg/kg, i.p.) administration. No behavioral, biochemical, and inflammatory abnormality was perceived in the brain tissues of experimental animals after LPS administration. l-cysteine precipitated marginal symptoms of toxicity in the brain tissue. Similar pattern of wholesome effect of LPS were perceived when evaluated through the brain tissue fatty acid profile, histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Various studies have reported the role of ROS in development of cancer manifested by the increase in TBARs, PC and reduction in the activity of SOD, GSH and Catalase [40,41]. Same type of manifestations in the antioxidant markers were also noted in DMBA treated rats.…”
Section: Discussionmentioning
confidence: 79%
“…Various studies have reported the role of ROS in development of cancer manifested by the increase in TBARs, PC and reduction in the activity of SOD, GSH and Catalase [40,41]. Same type of manifestations in the antioxidant markers were also noted in DMBA treated rats.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, the evaluation of antioxidant machinery in the mammary gland tissue of experimental animals is critical. Various studies have reported the role of ROS in cancer, manifested by an increase in TBARS and PC and a reduction in the activity of SOD, GSH, and catalase ( Tiwari et al, 2016 ; Al-Saeedan et al, 2018 ). The same type of antioxidant marker was also observed in the DMBA-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evaluation of antioxidant machinery in the mammary gland tissue of experimental animals is critical. Various studies have reported the role of ROS in cancer, manifested by an increase in TBARS and PC and a reduction in the activity of SOD, GSH, and catalase (Tiwari et al, 2016;Al-Saeedan et al, 2018). The same type of antioxidant marker was also observed in the DMBAtreated rats.…”
Section: Discussionmentioning
confidence: 66%